STUDY OF GRIDHRASI AS SCIATICA AND ROLE OF SCIATICA NERVE (GRIDHRASI) (International Journal of Ayurveda and Pharma Research, 2021)
Gridhrasi is such an entity enumerated into eighty types of Nanatmaja Vataj Vyadhies. It is characterized by its distinct pain emerging from buttock and goes towards the heel of afflicted area. On the basis of symptom complex it can be broadly correlated with disease Sciatica in modern science. Ayurveda is a simple practical science of life and its principles are universally applicable to each individual for day to day life. Ayurveda speaks of every elements and facts of human life. Each and every human being desires to live happy and comfortable life but it is not possible owing to multiple factors related with changing lifestyle, environmental factors etc. As the advancement of busy professional and social life improper sitting posture in offices, factories, continuous and over exertion, jerk movements during travelling and sports. All these factors create undue pressure to the spinal cord and play a chief role in producing low back ache and Sciatica.